Termite Resistance of Heat-Treated Eucalyptus OSB Bonded with Eco-Friendly Castor Oil Adhesive - Sugahara, Estefani S. [UNESP]; Dias, André M. A.; Maffioletti, Fernanda D.; Paes, Juarez B.; Christoforo, André L.; Botelho, Edson C. [UNESP]; Dias, Alfredo M. P. G.; Campos, Cristiane I. [UNESP] (Tech Science Press, 2024)
Over the last decade, the oriented strand board (OSB) market presented meaningful growth. However, as a wood-based product, because of its anatomical structure and chemical composition, OSB can be damaged by biodeter-ioration agents. Given that, the biodeterioration of OSB panels must be investigated to improve its durability. In this way, this work analyses the biological resistance against termites (Cryptotermes brevis and Nasutitermes cor-niger) of heat-treated OSB panels made with Eucalyptus wood glued with vegetable-based polyurethane-an eco-friendly and sustainable adhesive derived from castor oil. Various panels were produced with different layers compositions (face:core:face of 25:50:25 and 30:40:30) in wood mass proportion and were submitted to postpro-duction heat treatment (at 175°C and 200°C) replacing the use of chemical insecticides. The influence of the layers variation and heat treatment temperature were evaluated, and these results were compared with commercial panels (made from pinus wood with insecticide). The results showed that the heat treatment did not improve the resistance against termite attack. However, all the experimental panels presented a satisfactory performance that was compatible with the commercial panels produced with insecticide available in the Brazilian market. The combination of Eucalyptus wood and castor oil adhesive to produce OSB, in any variation of layer composition, demonstrated natural resistance against termite attack compatible with the commercial panels, even without using chemical additives to increase durability.
Keywords: Alternative raw materials; biodeterioration; castor oil adhesive; OSB panel; wood products